Enzyme Architecture: Remarkably Similar Transition States for Triosephosphate Isomerase-Catalyzed Reactions of the Whole Substrate and the Substrate in Pieces - Zhai, Xiang (American Chemical Society, 2014)
[Image: see text] Values of (k(cat)/K(m))(GAP) for triosephosphate isomerase-catalyzed reactions of (R)-glyceraldehyde 3-phosphate and k(cat)/K(HP(i))K(GA) for reactions of the substrate pieces glycolaldehyde and HPO(3)(2–) have been determined for wild-type and the following TIM mutants: I172V, I172A, L232A, and P168A (TIM from Trypanosoma brucei brucei); a 208-TGAG for 208-YGGS loop 7 replacement mutant (L7RM, TIM from chicken muscle); and, Y208T, Y208S, Y208A, Y208F and S211A (yeast TIM). A superb linear logarithmic correlation, with slope of 1.04 ± 0.03, is observed between the kinetic parameters for wild-type and most mutant enzymes, with positive deviations for L232A and L7RM. The unit slope shows that most mutations result in an identical change in the activation barriers for the catalyzed reactions of whole substrate and substrate pieces, so that the two transition states are stabilized by similar interactions with the protein catalyst. This is consistent with a role for dianions as active spectators, which hold TIM in a catalytically active caged form.